2019
DOI: 10.1007/s00064-019-0597-5
|View full text |Cite
|
Sign up to set email alerts
|

Supercapsular percutaneously assisted (SuperPath) approach in total hip arthroplasty

Abstract: ObjectivePortal assisted minimally invasive total hip arthroplasty without dislocation of the femoral head with preservation of the hip capsule and the external rotators in the lateral decubitus position for rapid recovery with the option of expandability to a mini posterior or classic posterolateral approach at any time.IndicationsPrimary and secondary arthritis of the hip, femoral head necrosis, femoral neck fracture.ContraindicationsSevere anatomical disorders of the proximal femur, congenital high hip dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…The SuperPath approach retains the muscles around the hip joint such as the external rotation muscle group, piriformis muscle, gluteus minor muscle, and gluteus medius muscle, ensuring the integrity of the front and rear of the hip capsule [33]. The surgery uses in situ resection of the femoral neck and femoral head instead of dislocation of the hip joint, so it has the characteristics of less trauma and high safety [20]. Meng et al prospectively analyzed the level of CK and in ammation after THA in SuperPath approach, and found that the levels of all serum markers in the SuperPath group were still relatively higher than those in the PLA group at all times [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SuperPath approach retains the muscles around the hip joint such as the external rotation muscle group, piriformis muscle, gluteus minor muscle, and gluteus medius muscle, ensuring the integrity of the front and rear of the hip capsule [33]. The surgery uses in situ resection of the femoral neck and femoral head instead of dislocation of the hip joint, so it has the characteristics of less trauma and high safety [20]. Meng et al prospectively analyzed the level of CK and in ammation after THA in SuperPath approach, and found that the levels of all serum markers in the SuperPath group were still relatively higher than those in the PLA group at all times [29].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Dr. James Chow rst reported the supercapsular percutaneously assisted total hip (SuperPath, MicroPort Orthopedics Inc., Arlington, TN) approach, which combines the advantages of the supercapsular (SuperCap, MicroPort Orthopedics Inc., Arlington, TN, USA) approach and the percutaneously assisted total hip (PATH, MicroPort Orthopedics Inc., Arlington, TN, USA ) approach [15]. The SuperPath technique reaches the hip joint capsule through the tissue gap between the gluteus medius and the piriformis, so this technique reduces need for cutting muscles and tendon to protect the external rotator muscle [19,20]. Previously reported that SuperPath technology has shown that the time to go to the ground is shortened, the hospital stay is short, the incidence of complications is low, and the in-hospital cost is low [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The common exclusion criteria were as follows: active infection; tumors; and hematologic diseases, such as blood coagulation disorders, thrombocytopenia, and other hemorrhagic disorders. The additional exclusion criteria for SuperPath were as follows: severe deformation of the proximal femur; congenital high hip dysplasia; and osteosynthesis of the proximal femur [ 15 ]. Variables, such as gender, age, height, weight, BMI, diagnoses, affected side, pre- and post-operative radiographic findings, pre-operative hemoglobin (Hb) concentrations, pre- and post-operative hematocrit (Hct), operative time, and transfusion blood volume were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…While performing the SuperPATH approach, we followed exactly the steps described by Chow [ 13 ]. There have been papers that describe various aspects of the initial technique in detail such as the placement of the acetabular cup [ 14 , 15 ]. Quitmann [ 14 ] describes the use of a guidance tower for placing the acetabular cup, while Della Torre et al [ 15 ] point out the importance of the transverse acetabular ligament.…”
Section: Technique Modificationsmentioning
confidence: 99%
“…If the broach was as deep in the femur as planned preoperatively, we proceeded to the neck cut using a double-sided blade. The cut was made using the proximal end of the broach for guidance [ 14 ]. The next X-ray was taken after the trial reduction of the hip.…”
Section: Technique Modificationsmentioning
confidence: 99%